Introduction of Neolophiotrema xiaokongense gen. et sp. nov. to the poorly represented Anteagloniaceae (Pleosporales, Dothideomycetes) - Ren, Guang-Cong; Wanasinghe, Dhanushka N.; Monkai, Jutamart; Hyde, Kevin D.; Mortimer, Peter E.; Xu, Jianchu; Pang, Aimin; Gui, Heng (Phytotaxa, 2021)
The monotypic Neolophiotrema (typified by N. xiaokongense) is introduced for a wood-inhabiting taxon classified in Dothideomycetes. The genus is characterized by, coriaceous, immersed to semi-immersed ascomata, hamathecium with cellular pseudoparaphyses and overlapping 1–2-seriate, hyaline ascospores. Phylogenetic analysis of combined SSU, LSU, ITS, tef1-α and rpb2 sequence data supports the placement of Neolophiotrema in Anteagloniaceae (Pleosporales). A morphology-based synopsis key is provided to facilitate the identification of species of Anteagloniaceae. The classification and nature of species boundaries in Anteagloniaceae are discussed.